Proses Clearance In/Out dalam Penanganan Docking Kapal TB Bomas Setia oleh PT. Anugerah Tirta Samudra - April Maulana Saputra; Galih Satriyo; Saiful Rohman; Jovie Candra Purnama (Indonesian Maritime Researchers and Lecturers, 2026)
This study aims to analyze the clearance in and clearance out service processes carried out by PT Anugerah Tirta Samudra in handling the docking of the tugboat TB. Bomas Setia and to identify the parties involved, in order to ensure compliance with maritime regulations and smooth operations. A descriptive qualitative method was employed, with data collected through field observation, in-depth interviews with three operational informants selected using purposive critical case sampling, and documentation studies of the vessel's certificates. The findings show that the agency workflow relies on the integrated Inaportnet system and unfolds through three main stages. First, clearance in covers arrival notification, document verification, and port health quarantine clearance. Second, the docking maneuvering stage involves securing a Movement Approval Letter (SPOG) before the vessel enters the shipyard. Third, post-repair clearance out includes conducting a sea trial, reactivating seaworthiness certificates, settling non-tax state revenue obligations, and obtaining the Sailing Approval Letter (SPB). The success of the entire process depends heavily on close coordination between the shipping agency and the Harbor Master and Port Authority Office, PT Pelindo, the Port Health Quarantine Office, the Indonesian Classification Bureau, and the shipyard.